Reliability and Validity of Modified Algometer in Abdominal Examination. (17th March 2016) - Ko, Seok-Jae; Kim, Honggeol; Kim, Seul-Ki; Park, Kyungmo; Lee, Jeungchan; Lee, Beom-Joon; Oh, Jayoung; Lee, Kyungjin; Park, Jae-Woo
Abstract : Objective . Abdominal examination (AE) is one of the essential diagnostic methods in traditional Korean medicine that has been widely used for deciding treatment, cause, and prognosis of the disease. AE majorly depends on the experience of practitioners; therefore, standardization and quantification of AE are desperately needed. However, few studies have tried to objectify AE and established its standard. We assessed the reliability and validity of newly developed diagnostic device for AE called modified algometer (MA). Methods . Thirty-six subjects with functional dyspepsia were allocated into one of 2 groups according to gold standard of AE: epigastric discomfort without tenderness (n = 23 ) group or epigastric discomfort with tenderness (n = 13 ) group. Pressure pain threshold was evaluated at participants' epigastric region with algometer and MA. We assessed reliability and validity (sensitivity and specificity) and calculated optimal cutoff value. Results . MA showed high intertrial reliability (ICC 0.849; 0.703–0.923;P < 0.000 ) and validity (sensitivity: 76.92%; specificity: 60.87%), and cutoff value was 330.0 mmHg. Algometer and MA showed moderate correlation (r = 0.583, P ≤ 0.00 0 ). Conclusion . MA can be reliable and valid diagnostic device for AE and has the possibility of practical use for quantification and standardization of AE.